2009
DOI: 10.1007/s10549-009-0555-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the histological size of the sentinel lymph node metastases using RT–PCR assay: a rapid tool to estimate the risk of non-sentinel lymph node invasion in patients with breast cancer

Abstract: Results: BLN positivity was reported in 19.6% of the patients for a sensitivity of 89%. BLN specificity (94.5%) and negative predictive value (97.5%) clearly demonstrated its reliability to guide ALND decision. All, except one, residual axillary metastases were found in BLN-positive patients.Considering the 78 patients with SLN positivity or discordant status according to both criteria, the metastases histological size was significantly correlated to the expression level of MG (ρ=0.62) and CK19 (ρ=0.64) genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Eight papers have been published evaluating the application of qRT–PCR, with promising results ( Table 3 )55–62. The overall sensitivity of qRT–PCR was 78–96 per cent, exceeding that of imprint cytology and frozen section.…”
Section: Molecular Techniques: Quantitative Reverse Transcriptase–polmentioning
confidence: 99%
“…Eight papers have been published evaluating the application of qRT–PCR, with promising results ( Table 3 )55–62. The overall sensitivity of qRT–PCR was 78–96 per cent, exceeding that of imprint cytology and frozen section.…”
Section: Molecular Techniques: Quantitative Reverse Transcriptase–polmentioning
confidence: 99%
“…Major advantages of this technique were portended to reduce the workload of pathologists involved in intraoperative analysis of pathology specimens and provide accurate rapid results to the operating surgeon [23]. Evidence also suggested that it could predict additional, non sentinel node metastases [26]. A contentious issue raised however, was the loss of tissue, as part or the entire sentinel node was required to be homogenised to perform the assay.…”
Section: Technical Pointsmentioning
confidence: 99%
“…On the other hand, a recent study by Veys et al [46] found most PCR-false-negative cases to be associated with borderline expression of genes that most likely corresponded to micrometastases, which appears reasonable since histological size of metastases in SLNs correlates with gene expression levels as measured by qRT-PCR [48,54].…”
Section: Discrepancies Between Histology and Rt-pcr Resultsmentioning
confidence: 87%
“…Secondly, according to Visser et al, the one-step nucleic acid amplification (OSNA) assay (Sysmex Corporation, Kobe, Japan) detects CK19 with high sensitivity (95%) and specificity (97%) after discordant case investigation [43][44][45]. However, since only a single marker is analysed, tumours might be missed, as reported by Veys et al [46] in their study of the BLN assay. RT-PCR for CK19 may sometimes generate false-positive results because of contamination with benign epithelial cells [37].…”
Section: Discussionmentioning
confidence: 99%